Heterozygous Deep‐Intronic Variants and Deletions in ABCA4 in Persons with Retinal Dystrophies and One Exonic ABCA4 Variant. Issue 1 (January 2015) - Bax, Nathalie M.; Sangermano, Riccardo; Roosing, Susanne; Thiadens, Alberta A.H.J.; Hoefsloot, Lies H.; van den Born, L. Ingeborgh; Phan, Milan; Klevering, B. Jeroen; Westeneng‐van Haaften, Carla; Braun, Terry A.; Zonneveld‐Vrieling, Marijke N.; de Wijs, Ilse; et al.
<x xml:space="preserve">Abstract</x> A person with Stargardt disease (STGD1) carries a deletion of exons 20‐22 in one of two ABCA4 gene copies and a deep‐intronic mutation (c.5196+1137G>A) in the other copy. Both types of mutations cannot be identified using standard Sanger sequencing of the protein coding segments of the gene and require specific analyses. Deletions and deep‐intronic variants in ABCA4 can constitute up to 20% of ABCA4 mutations. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>